Deterioration After Surgery for Degenerative Cervical Myelopathy: An Observational Study From the Canadian Spine Outcomes and Research Network. Issue 5 (1st March 2023) - Evaniew, Nathan; Burger, Lukas D.; Dea, Nicolas; Cadotte, David W.; Bailey, Christopher S.; Christie, Sean D.; Fisher, Charles G.; Rampersaud, Y Raja; Paquet, Jérôme; Singh, Supriya; Weber, Michael H.; Attabib, Najmedden; et al.
Abstract : Study Design: A Prospective cohort study. Objective: To investigate the incidence, etiology, and outcomes of patients who experience neurological deterioration after surgery for Degenerative Cervical Myelopathy (DCM). Summary of Background Data: Postoperative neurological deterioration is one of the most undesirable complications that can occur after surgery for DCM. Methods: We analyzed data from the Canadian Spine Outcomes and Research Network DCM prospective cohort study. We defined postoperative neurological deterioration as any decrease in modified Japanese Orthopaedic Association (mJOA) score by at least one point from baseline to three months after surgery. Adverse events were collected using the Spinal Adverse Events Severity protocol. Secondary outcomes included patient-reported pain, disability, and health-related quality of life. Results: Among a study cohort of 428 patients, 50 (12%) deteriorated by at least one mJOA point after surgery for DCM (21 by one point, 15 by two points, and 14 by three points or more). Significant risk factors included older age, female sex, and milder disease. Among those who deteriorated, 13 experienced contributing intraoperative or postoperative adverse events, six had alternative non-DCM diagnoses, and 31 did not have an identifiable reason for deterioration. Patients who deteriorated had significantly lower mJOA scores at one year after surgery [13.5 (SD 2.7) vs. 15.2 (SD 2.2), P <0.01 and those with larger deteriorations were less likely to recover their mJOA to at least their preoperative baseline, but most secondary measures of pain, disability, and health-related quality of life were unaffected. Conclusions: The incidence of deterioration of mJOA scores after surgery for DCM was approximately one in 10, but some deteriorations were unrelated to actual spinal cord impairment and most secondary outcomes were unaffected. These findings can inform patient and surgeon expectations during shared decision-making, and they demonstrate that the interpretation of mJOA scores without clinical context can sometimes be misleading.